1997
DOI: 10.1016/s0006-3495(97)78877-5
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond retinal structure changes in K-590 during the room-temperature bacteriorhodopsin photocycle: picosecond time-resolved coherent anti-stokes Raman spectroscopy

Abstract: Time-resolved vibrational spectra are used to elucidate the structural changes in the retinal chromophore within the K-590 intermediate that precedes the formation of the L-550 intermediate in the room-temperature (RT) bacteriorhodopsin (BR) photocycle. Measured by picosecond time-resolved coherent anti-Stokes Raman scattering (PTR/CARS), these vibrational data are recorded within the 750 cm-1 to 1720 cm-1 spectral region and with time delays of 50-260 ns after the RT/BR photocycle is optically initiated by pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
55
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 70 publications
9
55
0
Order By: Relevance
“…The fourth band at ~985 cm −1 , which we assign exclusively to K E , is not expected to be strong and is not seen at 77K in Raman 36,94 but was observed, in accord with our expectations, at room temperature in nanosecond time-resolved CARS 32 and Raman 22 at 984 cm −1 and at 987 cm −1 , respectively. The last two bands at 963 and 997 cm −1 in bacteriorhodopsin and at 954 and 992 cm −1 in xanthorhodopsin are present in both K 0 and K E states and exhibit no temperature dependence (Figure 4A).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The fourth band at ~985 cm −1 , which we assign exclusively to K E , is not expected to be strong and is not seen at 77K in Raman 36,94 but was observed, in accord with our expectations, at room temperature in nanosecond time-resolved CARS 32 and Raman 22 at 984 cm −1 and at 987 cm −1 , respectively. The last two bands at 963 and 997 cm −1 in bacteriorhodopsin and at 954 and 992 cm −1 in xanthorhodopsin are present in both K 0 and K E states and exhibit no temperature dependence (Figure 4A).…”
Section: Discussionsupporting
confidence: 89%
“…The last of the K states, K L , decays into L with a time constant of ~ 1.2 μs 83 . Two additional transitions were reported within the life-time of the K-like states with the time constants of (i) 30-70 ps 23,31,38 , and (ii) 50-250 ns 16,28,32 , respectively. We assign the former, with the τ 1 =50±20 ps time constant, to the K 0 -to-K E transition; the latter, with the τ 2 =150±100 ns time constant, had been already assigned to K E -to-K L transition 16,28 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The calculated IR spectra 29 indicated that the absorption maximum of the K L state is not as strongly bathochromically shifted, as the maximum of K E . Existence of K E and K L as separate intermediates was further supported by time-resolved CARS 33 , in which both the rate constant for the K E -to-K L transition and the main vibrational features of the K E and the K L were shown to be consistent with those in 29 .…”
Section: Introductionmentioning
confidence: 75%